Investigating ‘Too Big To Fail’: Should large banks be broken up? - Levy, Joshua (2012)
In this paper, a model based on the translog cost function was used to provide an insight into the controversy surrounding the government protection provided to banking institutions determined as ‘Too-big-to-fail’ (TBTF). Whilst the origins of this protection traces back to the bailout of Continental Bank in the US in 1984, the bailouts around the world during the financial crisis of 2007-2009 have established this issue as a major policy talking point. The support provided during the crisis was also in the form of assisted and facilitated mergers, which has actually resulted in many of these TBTF institutions becoming even larger, and has extended TBTF protection beyond commercial banking to investment banking and even insurance companies, as demonstrated by the bailout of AIG. The justification for such intervention to prevent failure is a desire to restore stability to financial systems and economies, whilst avoiding the damaging effects of contagion and spillovers to other interconnected firms. However, the consequence of such implicit state protection for institutions arises in the form of moral hazard, as the incentives of a bank’s creditors, depositors and management are distorted, alongside a weakening of market discipline. As such, TBTF institutions have access to a lower cost of capital than other firms, incentivizing it to increase the riskiness of its activities in the pursuit of higher returns. A much-cited justification for the scale of the largest banks around the world concerns economies of scale. This concept holds that the average costs of a firm fall as size increases, due to risk diversification and other factors. In this paper, I examine whether such scale economies actually exist, in the context of many calls from politicians for these institutions to be broken up, alongside a formal size limit of banks. Using a sample of UK banks, I fail to find evidence of economies of scale, instead finding evidence of diseconomies of scale. The presence of such decreasing returns to scale defies the much-cited rationale for consolidation and scale, consequently adding credence to the policy option of reducing bank size in order to remove the negative effects of TBTF institutions within a financial system. I also indentify a number of practical and methodological obstacles to the successful implementation of such a policy.